PENENTUAN PEAK GROUND ACCELERATION, RESPONS SPEKTRA DAN PEMBUATAN SYNTHETIC TIME HISTORIES UNTUK KOTA SEMARANG - Sandi Sadewa, Made
Abstract: Peak ground acceleration (PGA) for Semarang is developed probabilistically for engineering design purpose and improvement of the Seismic Resistance Building Code. The Seismic sources model the earthquake potential to a radius of about 500 km from Semarang and a depth of 200 km beneath ground surface. They include all subduction zones and shallow crustal of Indonesia. Two attenuation relation are chosen to appropriately represent subduction zone and shallow crustal fault for determination of ground motion. An attenuation relation proposed by Youngs (1997) is selected for subduction environments and an attenuation function proposed by Joyner and Boore (1997) for other seismic sources. Peak ground acceleration on base-rock for Semarang with 10% probability of exceedance in 50 year is then developed based upon the Gutenberg Richter magnitude vs. frequency relationship in combination with a Poison process mode. The analysis indicate that peak ground acceleration on the base-rock is 260 gal for 500 years return period. Target spectra for Semarang considering subduction and strike-slip mechanism were built and then use to generate synthetic time histories using SIMQKE program. Dynamic soil properties and synthetic time histories (output from SIMQKE program) were used as input for SHAKE91 program. The results are response spectra and peak ground acceleration at the ground surface for Semarang. In addition, results of the analysis in the form of amplification factor contours at ground surface are also generated.